An Ice Patch Artifact and Paleobiological Specimen from the Teton Mountains, Wyoming, USA - Sgouros, Rebecca A.; Stim, Matthew A. (Journal of Glacial Archaeology, 2016)
During the 2014 field season of the Teton Archaeological Project (TAP), twelve permanent snowfields and ice patches in the Teton Mountains were investigated for thawing organic artifacts and paleobiological specimens. During this survey, the TAP team identified two ice patches that contained faunal remains, non-cultural Douglas Fir (c. 6,000 cal. BP), and a possibly modified fragment of Whitebark Pine (c. 2,700 cal. BP). The results of this project demonstrate that ice patches have remained preserved in the Teton Range for at least 6,000 years and that organic artifacts and paleobiological specimens are actively thawing due to increasing temperatures. Furthermore, the data acquired from the organic ice patch material offers fresh information regarding the prehistoric use of high elevations in northwestern Wyoming during harsh climatic periods, and provides an environmental context for interpreting middle Holocene occupations above modern day tree line in the Teton Range.